The case of Cimpor and Camargo Correa : mergers and acquisitions - Ribeiro, João Augusto Clemente (2016)
Cement is an expanding industry dominated by emerging markets, which in 2011consumed 89% of the global demand. The industry has high barriers to entry and high initial investments which leads the market to be relatively concentrated among the biggest players. Therefore companies need to have high production capacities and diversified risk in order to be competitive. That was the solution found by the group Camargo Correa, to make a takeover over Cimpor that is a Portuguese company operating in eleven countries among four continents. Thereby the focus of my dissertation is to calculate both companies’ standalone values and subsequently synergies, within a goal of comparing my valuation with the price offered by the group Camargo Correa. Hence, Cimpor’s share price is considered to have a 5.18% upside potential and synergies of 0.58 Euros. This is equivalent to a total premium over Cimpor’s average share price in 2011 of 16, 58 %. Consequently in my point of view 5.91 Euros per share should have been the fair price offered by Camargo Correa to Cimpor. Nevertheless, compared with the price offered by Camargo Correa of 5, 5 there is a difference of 7.38% or 0.41 Euros per share, which I consider that, came from both an underestimation of the value of the synergies and Cimpor’s upside potential.